2010
DOI: 10.7601/mez.61.245
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of 8 household and hygiene insecticides against bedbug (Cimex lectularius)

Abstract: Abstract:The e$cacy of eight insecticides which are used as household and hygiene insecticides in Japan were evaluated against susceptible strain of bedbug (Cimex lectularius L.). d-d-t Cyphenothrin and fenitrothion showed high e$cacy among the six insecticides (d-d-t cyphenothrin, permethrin, d-phenothrin, fenitrothion, propoxur and metoxadiazon) by topical application test and filter paper contact test. By the test of oil formulation, imiprothrin showed the highest knock down activity and permethrin showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Moreover, using insecticides namely, pyrethroids, pyrroles, and neonicotinoids are the most common compounds for bed bug control (Sutherland et al 2015 andLee et al 2018). The previous studies indicate that the commercial insecticide products that containing d -d -t cyphenothrin, permethrin, d -phenothrin or fenitrothion have the ability to kill the bed bug (Okamoto et al 2010). These finding might be in agreement with the results of the present study.…”
Section: Resultssupporting
confidence: 94%
“…Moreover, using insecticides namely, pyrethroids, pyrroles, and neonicotinoids are the most common compounds for bed bug control (Sutherland et al 2015 andLee et al 2018). The previous studies indicate that the commercial insecticide products that containing d -d -t cyphenothrin, permethrin, d -phenothrin or fenitrothion have the ability to kill the bed bug (Okamoto et al 2010). These finding might be in agreement with the results of the present study.…”
Section: Resultssupporting
confidence: 94%
“…Taking into account our findings and those of the aforementioned studies, we can conclude that this mixture of a.i.s has the potential concerning stored-product pest management in storages. It can also be assumed that piperonyl butoxide, as an insecticide synergist that enhances the insecticidal properties of d-tetramethrin and acetamiprid [59,107], plays a significant role in the elevated efficacy of this mixture in this study, compared with the insecticidal properties of these a.i.s in former studies [108][109][110][111][112][113][114][115]. Previous research has revealed that the incorporation of piperonyl butoxide into pyrethroid insecticides did not alter the susceptibility of the susceptible strain of A. diaperinus [113].…”
Section: Discussionmentioning
confidence: 99%